PERANCANGAN SISTEM PEMBUATAN PEMBELAJARAN ELEKTRONIK PADA LEMBAGA BIMBINGAN BELAJAR D-LLA COURSE - SYAMSIAH SYAMSIAH (Faktor Exacta, 2014)
In order for students to have motivation in the learning process, the methods used in the learning process must be renewed tailored to the interests, intelligence and learning styles of students. One way by using appropriate instructional media that students are more active or a role in the learning process. As the development of Internet technology, e-learning system was developed, so the study and research is needed. The essence of e -learning is a form of conventional learning as outlined in digital format through internet technology. Therefore developing this system is not merely to present the course material in the internet but need to be considered logically. Similarly, the development of a simple design, personal and fast, and entertainment elements will make students learn at home in front of the net. In studies where the research was conducted with the e-learning system is a descriptive method, with data collection using questionnaires and interviews. For the media to be used by students and teachers, he built a Learning Management System. In addition it should be noted that the supporting infrastructure will support the development of e-learning system that dipilih. From system improvements and quality of learning expected learning outcomes expected to be the better Institutions Guidance learning D - LLA COURSE. Keywords: E - Learning, ANP Analysis, Learning Management System